Polemic of Indonesian Criminal Code Bill on Bali’s Tourism Industry - I Made Ari Kapela (Bali Tourism Board, 2019)
Indonesian Criminal Code Bill proposal, suddenly became a hot issue after Indonesia commemorate their 74th Independence Day. The executive and legislative accelerated completion of Indonesian Criminal Code Bill (ICCB) at Fairmont Hotel, Jakarta. Many parties have been urging the government to revise some outdated articles since the penal code was a product of Dutch colonialism in the past. Three crucial topics were discussed and added to the draft regarding blasphemy to president, crimes against morality and decency, as well as specific intent crime. Apparently, some parties were unsatisfied with the draft. Waves of uproar sprang up between mid-September and early October 2019. the demonstrators considered that there are ten controversial articles in the ICCB that have vague enforcement parameters. To reduce the public tension, the government agreed to delay the ICCB ratification that, according to public includes multiple problematic articles. President Joko Widodo stated that more input would be conducted before disseminate the latest ICCB information to public. The postponement would be evoked after the new set of parliaments is inaugurated. Albeit being postponed, Tourism practitioner in Bali experiencing significant loss of tourists visit due to the issues. It is expected in future; the government would involve tourism practitioner in group discussion before setting new regulations that may affect the vital industry of Indonesia.